Hydrogen bonding interactions between arsenious acid and dithiothreitol/dithioerythritol at different pH values: a computational study with an explicit solvent model. (18th October 2021) - Shen, Jinyu; Wu, Xiuxiu; Yu, Jinsong; Yin, Fengqin; Hao, Liling; Lin, Caixia; Zhu, Lizhi; Luo, Chunyan; Zhang, Changzhe; Xu, Fei
Abstract : Solvents participate in the most stable complex formation between arsenious acid and DTT/DTE in their optimal pH ranges. Abstract : Sulfhydryl compounds are regarded as potential functional monomers for arsenious acid imprinted polymers due to their high affinity to arsenious acid in aqueous solution. However, the recognition and binding mechanisms between arsenious acid and sulfhydryl compounds in solutions remain unclear. In this work, the binding interactions between arsenious acid and dithiothreitol (DTT)/dithioerythritol (DTE) in aqueous solution and HEPES buffer at different pH values were investigated using density functional theory (DFT) calculations. DTE binding complexes were calculated to be more energetically favorable than DTT. H3 AsO3 –DTE − –H2 O and H3 AsO3 –DTE–HEPES − complexes were shown to have the greatest affinity with the occurrence of deprotonation as pH changes. This indicates that the optimal pH ranges of binding between the template and monomer (DTT/DTE) in aqueous solution and HEPES buffer are 8.30–9.23 and 7.50–8.30, respectively. The reduced density gradient (RDG) method and non-covalent interaction (NCI) analysis demonstrated the presence of hydrogen bonds, van der Waals forces and repulsive forces in the systems. Energy decomposition analysis (EDA) predicted that the electrostatic force is the dominant composition of binding energy. The non-covalent properties of hydrogen bonds were further explained by the quantum theory of atoms in molecules (QTAIM) analysis. The calculated infrared (IR) spectrum reflected the formation of hydrogen bonds, which agreed well with the experimental IR spectrum. The change rate of the absorbance in ultraviolet-visible spectroscopy (UV-Vis) provided information for the best binding of H3 AsO3 –DTE in HEPES solution.